Studi Eksperimental Pengaruh Variasi Sudut Kemiringan Poros Terhadap Kinerja Turbin Ulir Archimedes - Kukuh Pribadi; Dedet Hermawan Setiabudi; Bahrul Jalaali (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2022)
This study aims to design and conduct an experimental study of axle tilt angles variation on the performance of the Archimedes screw turbine (AST). The AST was constructed based on Rorres (2000) [3] formulation to achieve the optimum design of AST. This design was obtained with the followings parameters: 1.7m turbine axle length, 0.069m and 0.128m of internal and external turbine radius, 0.260m pitch length, 6.5 pitches number, 59° and 72° of external and internal blade angel, and 2 number of blades. The screw turbine performance was experimentally carried out by varying the angle of the turbine axle in the range of 25°, 30°, 35°, 40°, and 45°. The test was utilized the natural river flow with an average discharge of 0.011 m3/s. The result was yielded that the optimum angle of the turbine was at a turbine tilt axle of 35° while the rotational speed was 265.5 rpm, whereby the turbine generated 48.81W power and 4.09Nm of torque. This study is hopefully beneficial for the turbine design reference as well as its experimental evaluation.